2015
DOI: 10.1007/s13277-015-3514-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum miR-483-5p: a novel diagnostic and prognostic biomarker for patients with oral squamous cell carcinoma

Abstract: Deregulation of microRNAs (miRNAs) is essential to tumor development, and serum miRNA profiles have been reported in several cancers. However, the serum miRNA profile in oral squamous cell carcinoma (OSCC) remained unclear. The present study aimed to explore abnormal miRNA profile in sera samples from OSCC patients and the association of miR-483-5p with patient prognosis. Microarray analysis was performed in sera from OSCC patients versus healthy controls. miR-483-5p expression was measured by reverse transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 15 publications
1
48
0
Order By: Relevance
“…Xu et al () found that miR‐483 expression was significantly increased in OSCC patients, which was significantly correlated with tumor nodal metastasis (TNM) stage. And multivariate analyses for overall survival revealed that high miR‐483 expression was an independent prognostic factor for OSCC (Xu et al, ). Down‐regulation of miR‐22 has been observed in the development of many types of cancer (Damavandi et al, ; Yang et al, ; Zhang, Xia, Tian, Liu, & Zhou, ; Zuo et al, ), and overexpression of miR‐22 suppressed the proliferation, migration and invasion of gastric cancer and renal carcinoma cells (Zhang, Zhang et al, ; Zuo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al () found that miR‐483 expression was significantly increased in OSCC patients, which was significantly correlated with tumor nodal metastasis (TNM) stage. And multivariate analyses for overall survival revealed that high miR‐483 expression was an independent prognostic factor for OSCC (Xu et al, ). Down‐regulation of miR‐22 has been observed in the development of many types of cancer (Damavandi et al, ; Yang et al, ; Zhang, Xia, Tian, Liu, & Zhou, ; Zuo et al, ), and overexpression of miR‐22 suppressed the proliferation, migration and invasion of gastric cancer and renal carcinoma cells (Zhang, Zhang et al, ; Zuo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…And U6 snRNA (small nuclear RNA) was used as an internal control. All miRNAs were measured by using the equation 2-ΔnormalCnormaltfalse(normalΔCt=CminormalRNA-Ct0.6emnormalU0.6em6false) .…”
Section: Methodsmentioning
confidence: 99%
“…And U6 snRNA (small nuclear RNA) was used as an internal control. All miRNAs were measured by using the equation 2 −∆C t (∆C t = C tmiRNA -C tU6 ) [13].…”
Section: Quantitative Real-time Pcr Verification Of Mirnasmentioning
confidence: 99%
“…Recently, miR-483-3p has been reported to be involved in the occurrence of many diseases, such as esophageal squamous cell carcinoma (19), cardiomyocyte apoptosis (20) and gastric cancer (21). It has also been shown to be dysregulated and associated with poorer disease-specific survival in various cancers (22)(23)(24)(25)(26). Although Song et al (24) reported that miR-483-5p can serve as a negative regulator of lung cancer metastasis suppressors RhoGDI1 and ALCAM, the role of miR-483 in lung disease particularly COPD and the molecular mechanisms by which miR-483 regulates such diseases are still not clear.…”
Section: Discussionmentioning
confidence: 99%